Serum levels of Organochlorine Pesticides and Breast Cancer Risk in Iranian Women - Paydar, Parisa; Asadikaram, Gholamreza; Fallah, Hossein; Zeynali Nejad, Hamid; Akbari, Hamed; Abolhassani, Moslem; Moazed, Vahid; Khazaeli, Payam; Heidari, Mahmoud Reza (Archives of environmental contamination and toxicology, 2019)
Breast cancer is a multifactorial disease and its etiology is linked to multiple risk factors. There are shreds of controversial evidence that exposure to organochlorine pesticides (OCPs) are important in the etiology of breast cancer. The present study aimed to determine the circulating levels of OCPs in patients with breast tumors in Southeastern of Iran. This case–control study included 27 patients with malignant breast tumors (MBT), 31 patients with benign breast tumors (BBT), and 27 healthy women as a control group. Serum OCPs levels, including α-hexachlorocyclohexane (α-HCH), β-HCH, γ-HCH, 2,4-dichlorodiphenyltrichloroethane (2,4-DDT), 4,4-DDT, 2,4-dichlorodiphenyldichloroethylene (2,4-DDE), and 4,4-DDE, were measured using gas chromatography. Our data revealed significantly higher concentrations of 2,4-DDT in MBT and BBT groups compared with control ones ( P < 0.001 for both comparisons). Patients with breast cancer suffered significantly higher accumulation levels of 4,4-DDE compared with control subjects ( P = 0.04). Significant correlations were found among organochlorine compounds with each other in both patients’ groups. There was a significant positive correlation between body mass index and serum levels of 2,4-DDT in BBT group ( r = 0.407, P = 0.02). The present findings suggest that the serum levels of 4,4-DDE and 2,4-DDT are associated with an increase in the risk of breast cancer in Southeastern women of Iran.